Kedudukan Hukum Pihak Ketiga dalam Layanan Keuangan Tanpa Kantor - Joko Suryono, Leli; Anggriani, Reni (Jurnal Media Hukum, 2018)
Financial Services Authority Regulation Number 19/POJK.03/2014 concerning Financial Services Without Offices In the Context of Inclusive Finance, the Financial Services Authority in collaboration with the Banking sector makes services sell well. In this study as clever behavior is Bank Central Asia, which is one of the banks that conducts Officeless Financial Services, because it needs to serve people in remote areas, it is necessary to know the definition of clever service in order to know how the legal position of Third Parties in managing smart services still unclear, especially the legal status of the Third Party as a liaison between the bank and the customer. The purpose of the study is to examine and analyze the legal standing of third parties in financial services without offices. This research is a normative legal research that examines the principles, legal concepts and legislation related to the legal position of third parties in the provision of financial services without offices. The conclusion of this study is that Officeless Financial Services is an activity of providing banking services and/or other financial services carried out not through office networks and legal relations of the parties based on cooperation agreements and internal circulars. The legal position of third parties is as a bank liaison with customers (agents) and an extension of the bank (partner), where in each implementation there are rights and obligations that must be fulfilled in order to achieve the implementation of salable services.